Impact of weight on the efficacy and safety of direct-acting oral anticoagulants in patients with non-valvular atrial fibrillation: a meta-analysis. Issue 3 (27th January 2020) - Malik, Aaqib H; Yandrapalli, Srikanth; Shetty, Suchith; Aronow, Wilbert S; Jain, Diwakar; Frishman, William H; Cooper, Howard A; Panza, Julio A
Abstract: Aims: This study sought to determine the impact of weight and body mass index (BMI) on the safety and efficacy of direct-acting oral anticoagulants (DOACs) compared with warfarin in patients with non-valvular atrial fibrillation. Methods and results: A systematic literature search was employed in PubMed, Embase, and Cochrane clinical trials with no language or date restrictions. Randomized trials or their substudies were assessed for relevant outcome data for efficacy that included stroke or systemic embolization (SSE), and safety including major bleeding and all-cause mortality. Binary outcome data and odds ratios from the relevant articles were used to calculate the pooled relative risk. For SSE, the data from the four Phase III trials showed that DOACs are better or similarly effective with low BMI 0.73 (0.56–0.97), normal BMI 0.72 (0.58–0.91), overweight 0.87 (0.76–0.99), and obese 0.87 (0.76–1.00). The risk of major bleeding was also better or similar with DOACs in all BMI subgroups with low BMI 0.62 (0.37–1.05), normal BMI 0.72 (0.58–0.90), overweight 0.83 (0.71–0.96), and obese 0.91 (0.81–1.03). There was no impact on mortality in all the subgroups. In a meta-regression analysis, the effect size advantage of DOACs compared with warfarin in terms of safety and efficacy gradually attenuated with increasing weight. Conclusion: Our findings suggest that a weight-based dosage adjustment may be necessary to achieve optimal benefits of DOACs for thromboembolic prevention in these patients with non-valvular atrial fibrillation. Further dedicated trials are needed to confirm these findings. PROSPERO 2019 CRD42019140693. Available from: https://www.crd.york.ac.uk/prospero/display_record.php? ID=CRD42019140693 .